The Efficacy of Bank Mergers in Canada: The Case of the Bank of Montreal and Royal Bank Merger - Kapooh, Rajat (Université Concordia, 1999)
Keywords: Banque Royale; Banque de Montréal; Banques

Analyse du projet de fusion entre Groupe financier Banque Royale, Banque de Montréal - Massicotte, Marie (Université Laval, 1999)
Keywords: Banque Royale; Banque de Montréal; Banques

Bank of Montreal and Royal Bank: A Critical Study of Merger - Rahman, Mohammad Anamur (Université Concordia, 1999)
Keywords: Banque Royale; Banque de Montréal; Banques

La première caisse populaire de Montréal fut fondée par des leaders du mouvement ouvrier - Bélanger, Guy (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1998)
Keywords: Caisses populaires; Desjardins, Alphonse

MACAULAY, ROBERTSON - Boucher, David C. (Dictionnaire biographique du Canada, 1998)

FORGET, LOUIS-JOSEPH - Jedwad, Jack (Dictionnaire biographique du Canada, 1998)

FORGET, sir RODOLPHE - Jedwad, Jack (Dictionnaire biographique du Canada, 1998)

CLOUSTON, sir EDWARD SEABORNE - Miller, Carman (Dictionnaire biographique du Canada, 1998)

OUIMET, JOSEPH-ALDRIC - Munro, Kenneth (Dictionnaire biographique du Canada, 1998)

Montréal dans le système-monde: ville internationale ou métropole nord-américaine - Polèse, Mario (Montréal 2001. Visages et défis d'une métropole, 1998)
Keywords: Métropole

City Management and the Emerging Welfare State: Evolution of City Budgets and Civic Responsibilities in Montreal, 1931-1951 - Collin, Jean-Pierre (Journal of Policy History, 1997)

Analyse comparative de Montréal et Vancouver en tant que villes accueillant des centres financiers internationaux (CFI) - Dumont, Sonia (Université Laval, 1997)

Les rapports médecins-infirmières et l'implication de la Métropolitaine dans la lutte contre la mortalité infantile, 1909-53 - Baillargeon, Denyse (Canadian Historical Review, 1996)
Keywords: Assurance; Enfants; Infirmières; La Métropolitaine; Mortalité; Médecine

Montréal... l'histoire oubliée (Histoire Québec, 1996)
Keywords: Arts sacrés; Leduc, Ozias; Musées; Peinture; Églises

La fabrication des timbres-poste canadiens et des billets de banque à Montréal de 1871 à 1889: la British American Bank Note - Caron, Normand (Histoire Québec, 1996)
Keywords: Banques; Imprimerie; Poste

Price Discovery Around Canadian Equity Trading Halts Using Intraday Data - Nemiroff, Howard B. (Université Concordia, 1996)

Du projet de reconquête économique à l'idée de management: un bilan des études consacrées au mouvement Desjardins - Rousseau, Yvan (Histoire sociale / Social History, 1996)
Keywords: Banques; Caisses populaires

An Analysis and Evaluation of the Strategic Planning and Strategic Management Processes at the Standard Life Assurance Company - Poirier, Bruce R. (Université Concordia, 1995)
Keywords: Assurance

DRUMMOND, sir GEORGE ALEXANDER - Brassard, Michèle; Hamelin, Jean (Dictionnaire biographique du Canada, 1994)

OGILVIE, ALEXANDER WALKER - Brassard, Michèle; Hamelin, Jean (Dictionnaire biographique du Canada, 1994)

DAWES, JAMES PAWLEY - Burr, Gordon (Dictionnaire biographique du Canada, 1994)

ARCHAMBAULT, LOUIS - Comeau, Robert (Dictionnaire biographique du Canada, 1994)

GRENIER, JACQUES - Desrochers, Luc (Dictionnaire biographique du Canada, 1994)

L'attitude des chinois de Montréal vis-à-vis des stratégies ethniques des banques - Hakimian, Edith (École des hautes études commerciales de Montréal, 1994)
Keywords: Banques; Chinois

JOSEPH, JACOB HENRY - Jedwab, Jack (Dictionnaire biographique du Canada, 1994)

LE MOYNE DE MARTIGNY, VITE-ADÉLARD - Paré, Jean-Pierre (Dictionnaire biographique du Canada, 1994)

SAINT-CHARLES, FRANÇOIS-XAVIER - Rudin, Ronald (Dictionnaire biographique du Canada, 1994)

ROYAL, JOSEPH - Silver, A. I. (Dictionnaire biographique du Canada, 1994)

Prêtres et prêteurs au XIXe siècle - Hudon, Christine (Histoire sociale / Social History, 1993)

Les contraintes structurelles des finances publiques locales: les budgets municipaux dans la région de Montréal, en 1991 - Collin, Jean-Pierre; Hamel, Pierre J. (Recherches sociographiques, 1993)
Keywords: Fiscalité

L'évolution de l'assurance contre l'incendie au Canada: avant 1804 et de 1804 à 1867 - Parizeau, Gérard (Assurances, 1993)
Keywords: Assurance; Incendies

Les infirmières de la Métropolitaine au service des Montréalaises - Baillargeon, Denyse (Les Bâtisseuses de la Cité, 1993)
Keywords: Assurance; Femmes; Infirmières

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

The Evolution of Corporate Debt Issues in Canada from 1970 to 1991 and its Impact on Debt Trusteeships - Lochhead, Louis (Université Concordia, 1993)

Banque royale: au cœur de l'action - McDowall, Duncan (Éditions de l'Homme, 1993)
Keywords: Banque Royale; Banques

Quick to the Frontier: Canada's Royal Bank - McDowall, Duncan (McClelland & Stewart, 1993)
Keywords: Banque Royale; Banques

L'évolution de l'assurance contre l'incendie au Canada: troisième période: de 1867 à nos jours - Parizeau, Gérard (Assurances, 1993)
Keywords: Assurance; Incendies

L'arme favorite de l'épicier indépendant: éléments d'une histoire sociale du crédit (Montréal, 1920-1940) - Taschereau, Sylvie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1993)
Keywords: Épicerie

La Banque du Canada: origines et premières années / The Bank of Canada: Origins and Early History - Watts, George S. (Carleton Library, 1993)

L'expansion des caisses populaires à Montréal, 1940-1960 - Linteau, Paul-André (Coopératives et développement, 1992)
Keywords: Banques; Caisses populaires

La doyenne des banques québécoises: la Banque de Montréal - Paré, Jean-Pierre (Cap-aux-Diamants, 1992)
Keywords: Banque de Montréal; Banques

Les origines des banques canadiennes - Perry, J. Harvey (Le Banquier, 1991)
Keywords: Banques

100 ans d'histoire: revue de l'exercice 1991 - Association des banquiers canadiens (Association des banquiers canadiens, 1991)
Keywords: Banques

Façades des 43-59, rue Saint-Jacques Ouest - Lachapelle, Jacques (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Banques; Patrimoine

Le crédit dans une caisse populaire en milieu urbain: Saint-Alphonse d'Youville, 1940-1950 - Poirier, Jean (Université du Québec à Montréal, 1991)
Keywords: Banques; Caisses populaires; Saint-Alphonse-d'Youville (paroisse)

Desjardins et les Caisses Populaires 1900-1920, naissance et développement d'un mouvement coopératif - Poulin, Pierre (Université Laval, 1991)
Keywords: Banques; Caisses populaires; Desjardins, Alphonse

Par l'ordre et par l'économie. Les Caisses d'épargne et l'État au Québec (1819-1871) - Vanasse, Frédéric (Université du Québec à Montréal, 1991)
Keywords: Banques

L'encadrement de la maternité au Québec entre les deux guerres: les gardes de La Métropolitaine, les Gouttes de lait et l'Assistance maternelle - Baillargeon, Denyse (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1990)
Keywords: Assistance maternelle; Assurance; Enfants; Femmes; Goutte de lait; Infirmières; La Métropolitaine

McDOUGALL, JOHN - Milot, Maurice (Dictionnaire biographique du Canada, 1990)

HUDON, VICTOR - Rudin, Ronald E. (Dictionnaire biographique du Canada, 1990)

KING, EDWIN HENRY - Rudin, Ronald E. (Dictionnaire biographique du Canada, 1990)

STARNES, HENRY - Rudin, Ronald E. (Dictionnaire biographique du Canada, 1990)

SHANLY, WALTER - Stanley, Laurie C.C.; Blackwell, John D. (Dictionnaire biographique du Canada, 1990)